2017
DOI: 10.1177/1470320317741066
|View full text |Cite
|
Sign up to set email alerts
|

Association between TNF-a promoter -308G/A polymorphism and essential hypertension in the Asian population: A meta-analysis

Abstract: Objective:The results of studies on the association between tumor necrosis factor-a -308G/A (TNF-a -308G/A) polymorphism, and susceptibility to essential hypertension are controversial. To derive a more precise estimation, we conducted a meta-analysis of all similar articles.Methods:The summary effect odds ratios and 95% confidence intervals were obtained. Funnel plots and Egger’s test were used to estimate publication bias, and heterogeneity was assessed by the chi-square-based Q-test and I2 test.Results:Nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
2
5
0
1
Order By: Relevance
“…For the TNF-α -308G/A polymorphism, it was discovered that the GA and AA genotypes interacted with hypertension and hyperlipidemia to increase the risk of developing IS. The TNF-α -308 GA + AA genotypes were found to be associated with the risk factor of hypertension in the Asian population, which is consistent with the current findings ( 30 ). The TNF-α -308 A allele also appeared to have a higher risk of stroke when patients also had fever ( 56 ) and showed an increased risk of MI when combined with obesity ( 57 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For the TNF-α -308G/A polymorphism, it was discovered that the GA and AA genotypes interacted with hypertension and hyperlipidemia to increase the risk of developing IS. The TNF-α -308 GA + AA genotypes were found to be associated with the risk factor of hypertension in the Asian population, which is consistent with the current findings ( 30 ). The TNF-α -308 A allele also appeared to have a higher risk of stroke when patients also had fever ( 56 ) and showed an increased risk of MI when combined with obesity ( 57 ).…”
Section: Discussionsupporting
confidence: 92%
“…For the TNF-α-308G/A polymorphism, it was discovered that the GA and AA genotypes interacted with hypertension and hyperlipidemia to increase the risk of developing IS. The TNF-α-308 GA + AA genotypes were found to be associated with the risk factor of hypertension in the Asian population, which is consistent with the current findings (30).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although the results are inconsistent, many large studies showed some of FTO genotypes significantly increased risks of hypertension ( 45 ). Many other genes, such as MC4R ( 46 48 ), TNF-α ( 49 51 ), LEP ( LEPR ) ( 52 – 56 ) and β2AR ( 57 , 58 ), were all associated with both obesity and hypertension. However, because of the lack of comparable co-twin studies, the roles of shared genetic factors in the relationship between overweight or obesity and hypertension are still needed to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…Examination of TNF-α and IL-10 revealed that TNF-α expression increased and IL-10 expression decreased in the ALI group. As a proinflammatory mediator, TNF-α causes severe damage to pulmonary microvascular endothelial cells and alveolar epithelial cells, causing cell apoptosis, vascular damage, and thrombosis, increasing lung tissue permeability and hypoxia [25,26]. At the same time, TNF-α can promote the release of a variety of inflammatory mediators and further expand the inflammatory response, thereby aggravating lung tissue damage [27,28].…”
Section: Discussionmentioning
confidence: 99%